Mass spectrometry in drug metabolism and disposition - Lee, Mike S.; Zhu, Mingshe (Hoboken, N.J. : John Wiley, 2011)
"This book examines the background, industrial context, process, analytical methodology, and technology of metabolite identification. It emphasizes the applications of metabolite identification in drug research. While primarily a textbook, the book also functions as a comprehensive reference to those in the industry. The authors have worked closely together and combine complementary backgrounds to bring technical and cultural awareness to this very important endeavor while serving to address needs within academia and industry It also contains a variety of problem sets following specific sections in the text"--Provided by publisher.
Keywords: Drugs; Metabolites; Mass spectrometry; Pharmaceutical Preparations; Biopharmaceutics; Drug Design; Mass Spectrometry; Pharmacokinetics